PEMBUKUAN PRAKTIS DENGAN APLIKASI CATATAN KEUANGAN HARIAN PADA UMKM RUMAH MAKAN PRASMANAN MELAYU 7 - Munaf, Tommy; Elvina, Elvina (Jurnal Pengabdian, Pembelajaran dan Pemberdayaan Ekonomi Masyarakat (JP3EM), 2024)
This Community Service Activity (PKM) aims to find out the implementation of the opening with the application of Daily Financial Records in UMKM Malay Buffet Restaurant 7 West Tanjungpinang Village. Using the Daily Financial Records application can make it easier for business owners to record transactions quickly and easily. Simply by inputting transaction data such as sales, expenses and payables/receivables into the features available in the application, a transaction report has been generated and can be downloaded in PDF or Excel format according to the required date. The reports that can be downloaded include: Profit and Loss Reports, Accounts Payable Reports, and Customer Reports. The method of implementing the activities used in this PKM is a qualitative descriptive assumption method, data collection techniques using observation, interviews and documentation. The result of this PKM activity is that UKM Malay Buffet Restaurant 7 has been given an explanation on the use of digital financial report bookkeeping with the Daily Financial Record Application media and made brochures as information media in understanding how to use the daily financial record application